Metabolic pseudoprogression in a patient with metastatic KIT exon 11 GIST after 1 month of first-line imatinib: a case report - Tassinari, Elisa; Conci, Nicole; Battisti, Giacomo; Porta, Francesco; Di Scioscio, Valerio; Pirini, Maria Giulia; de Biase, Dario; Nigro, Maria Concetta; Iezza, Miriam; Castagnetti, Fausto; Lovato, Luigi; Fanti, Stefano; et al. (Frontiers in Oncology, 2023)
Positron emission tomography (PET) with 18-fluorodeoxyglucose ( 18 FDG) has proven to be highly sensitive in early assessment of tumor response in gastrointestinal stromal tumors (GIST), especially in cases where there is doubt, or when early prediction of the response could be clinically useful for patient management. As widely known, kinase mutations have an undoubtful predictive value for sensitivity to imatinib and the inclusion of KIT and PDGFRa mutational analysis in the diagnostic work-up of all GIST is now considered as standard practice.Herein we detailed described a case of an exon 11 KIT mutated-metastatic GIST patient, who presented an unexpected metabolic progression at the early 18 FDG-PET evaluation after one month of first line imatinib, unconfirmed at the liver biopsy performed near after, which has conversely shown a complete pathological response.This report aims to be aware of the existence of this metabolic pseudoprogression in GIST at the beginning of imatinib therapy, in order to avoid early treatment discontinuation. Therefore, an early metabolic progression during a molecular-targeted therapy always deserves to be evaluated in the context of the disease molecular profiling and in case of discordant finding between functional imaging and molecular background, a short-term longitudinal control should be suggested.